PPBP and DEFA1/DEFA3 genes in hyperlipidaemia as feasible synergistic inflammatory biomarkers for coronary heart disease - Yaowapa Maneerat; Kriengchai Prasongsukarn; Surachet Benjathummarak; Wilanee Dechkhajorn (Lipids in Health and Disease, 2017)
Abstract Background Coronary heart disease (CHD) is an important complication of atherosclerosis. Biomarkers, which associate with CHD development, are potential to predict CHD risk. To determine whether genes showing altered expression in hyperlipidaemia (H) and coronary heart disease (CHD) patients compared with controls could be CHD risk biomarkers. Methods Control, H, and CHD groups represented atherosclerosis to CHD development. Gene profiling was investigated in peripheral blood mononuclear cells using DNA microarrays. Eight selected genes expressed only in H and CHD groups were validated by real-time quantitative reverse transcription PCR and plasma protein determination. Results α-defensin (DEFA1/DEFA3), pro-platelet basic protein (PPBP), and beta and alpha2 hemoglobin mRNA expression was significantly increased in H and CHD groups compared with controls, but only plasma PPBP and α-defensin proteins were correspondingly increased. Conclusion PPBP and DEFA1/DEFA3 could be potential CHD biomarkers in Thai hyperlipidaemia patients.